Exploring the Impact of Organizational Well-Being on Intention to Leave the Nursing Profession: a Scoping Review - Rossella Roberta Basso; Valerio Della Bella; Jacopo Fiorini; Alessandro Sili (Infermieristica Journal)
Introduction. In several countries, the desire among nurses to leave their profession is a significant concern. Recent studies highlight a relationship between the nursing working context and the intention to leave the profession, indicating that suboptimal working conditions significantly influence the willingness to remain a nurse. This literature review aims to define the relationship between nurses' organizational well-being and intention to leave the profession, analyzing which organizational well-being variables influence this decision.